2001
DOI: 10.1007/s002320010054
|View full text |Cite
|
Sign up to set email alerts
|

Gramicidin-Perforated Patch Analysis on HCO 3 − Secretion Through a Forskolin-Activated Anion Channel in Rat Parotid Intralobular Duct Cells

Abstract: Forskolin-induced anion currents and depolarization were investigated to clarify the mechanism of HCO3- secretion in the intralobular duct cells of rat parotid glands. Anion currents of the cells were measured at the equilibrium potential of K+, using a gramicidin-perforated patch technique that negligibly affects intracellular anion concentration. The forskolin-induced anion current was sustained and significantly (54%) suppressed by glibenclamide (200 microM), a blocker of the cystic fibrosis transmembrane c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Our findings thus accord with the results of earlier, more detailed studies of cells isolated from adult animals that identified CFTR-like anion channels in distal lung epithelial cells (16,29). However, in our hands, the cAMP-evoked increase in G Cl Ϫ consisted of an initial peak followed by a slower, more sustained phase, whereas previous studies of anion currents flowing through CFTR-like channels have reported that cAMP causes a much more sustained response (12,16). The reason for this discrepancy between these two studies is unknown but may reflect the different origin of the cells used in the two studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings thus accord with the results of earlier, more detailed studies of cells isolated from adult animals that identified CFTR-like anion channels in distal lung epithelial cells (16,29). However, in our hands, the cAMP-evoked increase in G Cl Ϫ consisted of an initial peak followed by a slower, more sustained phase, whereas previous studies of anion currents flowing through CFTR-like channels have reported that cAMP causes a much more sustained response (12,16). The reason for this discrepancy between these two studies is unknown but may reflect the different origin of the cells used in the two studies.…”
Section: Discussionsupporting
confidence: 92%
“…The details have already been described in a previous report [18]. Briefly, gramicidin D (Sigma) was dissolved in methanol (10 mg/ml) and diluted 100 times with a standard KCl-rich pipette solution.…”
Section: Membrane Potential Measurementsmentioning
confidence: 99%
“…The membrane potential of submandibular acinar cells was measured using a whole cell patch-clamp technique [18]. The resting membrane potential was approximately -40 to -50 mV.…”
Section: Membrane Potential Measurementmentioning
confidence: 99%
“…Cl − secretion can be measured as Cl − secretory currents by using the gramicidin-perforated patch-clamp technique (14,15,32,34 -activated Cl − currents. A patch/whole-cell clamp amplifier (CEZ-2400; Nihon Kohden, Tokyo, Japan) was used to measure whole-cell currents.…”
Section: +mentioning
confidence: 99%
“…All measurements of the oscillatory Cl − secretory current were performed with the gramicidin-perforated patch-recording method (14,15,32,34). A pipette solution containing 150 mM KCl, 10 mM HEPES, and 0.1 mg/mL gramicidin D (Sigma-Aldrich) was adjusted to pH 7.4 using KOH.…”
Section: Measurement Of the Oscillatory CLmentioning
confidence: 99%